2014
DOI: 10.1007/s12011-014-0105-6
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Ca2+ Signals Involved on Cadmium-Induced Apoptosis in Rat Hepatocyte

Abstract: Cadmium (Cd) is an important industrial and environmental pollutant. In animals, the liver is the major target organ of Cd toxicity. In this study, rat hepatocytes were treated with 2.5∼10 μM Cd for various durations. Studies on nuclear morphology, chromatin condensation, and apoptotic cells demonstrate that Cd concentrations ranging within 2.5∼10 μM induced apoptosis. The early-stage marker of apoptosis, i.e., decreased mitochondrial membrane potential, was observed as early as 1.5 h at 5 μM Cd. Significant (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 36 publications
0
32
0
1
Order By: Relevance
“…Cd is known to induce cytotoxic injury via various cell signal-transduction pathways. Wang et al [40] demonstrated that Cd induced apoptosis via oxidative stress and calcium overload in rat hepatocytes, while Xu et al [41] have demonstrated that Cd resulted in the caspase-dependent apoptosis of neuronal cells, which was induced by [Ca 2+ ] i elevation, implicating ROS and activated MAPK and mTOR pathways. MAPKs are important signaling enzymes that play a critical role in controlling gene expression, cell survival and cell death; however, the regulation of cytotoxic injury by MAPKs is complex [12].…”
Section: Discussionmentioning
confidence: 99%
“…Cd is known to induce cytotoxic injury via various cell signal-transduction pathways. Wang et al [40] demonstrated that Cd induced apoptosis via oxidative stress and calcium overload in rat hepatocytes, while Xu et al [41] have demonstrated that Cd resulted in the caspase-dependent apoptosis of neuronal cells, which was induced by [Ca 2+ ] i elevation, implicating ROS and activated MAPK and mTOR pathways. MAPKs are important signaling enzymes that play a critical role in controlling gene expression, cell survival and cell death; however, the regulation of cytotoxic injury by MAPKs is complex [12].…”
Section: Discussionmentioning
confidence: 99%
“…Typical morphological changes associated with apoptosis were observed in chicken splenic lymphocytes treated with Cd, including membrane bleeds and overall cell shrinkages [17]. Oxidative stress and Ca 2+ signaling pathways have been also suggested as having a significant role in Cd-induced apoptosis [35]. …”
Section: Introductionmentioning
confidence: 99%
“…It is reported that Cd 2+ induces the apoptosis in the rat hepatocyte (Wang et al, 2014) and rat cerebral cortical neurons .…”
Section: 1 Analysis Of Cell Ultrastructurementioning
confidence: 99%
“…Such oxidative damage is very common during heavy metal treatment (Evlard et al, 2014;Wang et al, 2014). Metal ions can be oxidized or reduced by oxidoreductase in order to repair the damage to the cell and to detoxify.…”
Section: 21 Analysis Of Proteins With the Same Expression Tendencymentioning
confidence: 99%